Architectural Metaphor of A.A. Navis’s Works in Designing a Literary Appreciation Center in Yogyakarta - Alan Sastera Budiman (Jurnal Teknologi Riset Terapan, 2026)
Purpose: Yogyakarta, a leading Indonesian literary centre, lacks a purpose-built facility for literary appreciation activities such as reading, discussion, performance, and critical engagement. This study designs a Literary Appreciation Building accommodating these activities through an architectural metaphor inspired by A.A. Navis's Robohnya Surau Kami, translating its literary values into architectural form.Research Methodology: A qualitative design methodology employed a paradigm to concept framework, comprising thematic analysis of the short story, application of Antoniades's in 1990 Intangible Metaphor framework, and site analysis to develop strategies for massing, landscape, circulation, organisation, structure, and materials.Results: The design proposes a two-mass building on a 1.9-hectare site in Pakualaman, Yogyakarta, with a gross floor area of 3,809 m². The main building reflects the collapsing surau through a twisted façade, while the auditorium represents Ajo Sidi through a slanted roof and curved form. A pedestrian bridge connects both masses, symbolising reconciliation.Conclusions: The Intangible Metaphor approach proposed by Antoniades in 1990 effectively translates literary values into architectural design, enabling the building to embody its literary subject.Limitations: This study presents a conceptual design; construction and post-occupancy evaluation are needed to validate its effectiveness.Contributions: This study presents a replicable method for translating literary metaphor into architecture, contributing to the application of intangible metaphor in cultural building design.